2020
DOI: 10.1155/2020/2560174
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advance in Source, Property, Differentiation, and Applications of Infrapatellar Fat Pad Adipose-Derived Stem Cells

Abstract: Infrapatellar fat pad (IPFP) can be easily obtained during knee surgery, which avoids the damage to patients for obtaining IPFP. Infrapatellar fat pad adipose-derived stem cells (IPFP-ASCs) are also called infrapatellar fat pad mesenchymal stem cells (IPFP-MSCs) because the morphology of IPFP-ASCs is similar to that of bone marrow mesenchymal stem cells (BM-MSCs). IPFP-ASCs are attracting more and more attention due to their characteristics suitable to regenerative medicine such as strong proliferation and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 112 publications
0
22
0
Order By: Relevance
“…Moreover, during the last years, research has focused on the study of IFP-derived stem cells for regenerative medicine [ 15 ]. Recently, we showed that OA-IFP stem cells seem to be primed by the pathological environment and to exert incomplete protective activity from OA inflammation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the last years, research has focused on the study of IFP-derived stem cells for regenerative medicine [ 15 ]. Recently, we showed that OA-IFP stem cells seem to be primed by the pathological environment and to exert incomplete protective activity from OA inflammation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the knee joint, this results in distress for residents' cellular elements, including OA-IPFP stem cells. Zhong et al [1] correctly pointed out for the IPFP stem cells a probable reduction in chondrogenic differentiation potential induced by the OA environment; however, our in vitro data [3] also advocated that the ultrastructural, immunophenotypic, and functional characteristics of the OA-IPFP stem cells can be affected.…”
mentioning
confidence: 67%
“…A review article recently published by Zhong et al [1] interestingly considered the knee adipose tissue infrapatellar fat pad (IPFP) as a significant reservoir of mesenchymal stem cells (MSCs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The approach of leveraging the body’s innate regenerative potential with biomaterials and bioactive cues to direct endogenous stem/progenitor cells to injured sites to assist with tissue repair is a recent trend in regenerative medicine ( Gaharwar et al, 2020 ). Infrapatellar fat pad adipose-derived stem cells (IPFSCs), which reside in the site near articular cartilage, have attracted increasing attention due to their easy availability, rich quantity in autologous tissue, superior chondrogenic effects, less hypertrophy risk, inflammatory modulation, anti-senescence effects, cytokine secretion, and better scaffold culturing performance ( Hindle et al, 2017 ; Zhong et al, 2020 ). However, the migration of IPFSCs as well as other endogenous MSCs naturally occurs during a short time window only and does not sufficiently repair the cartilage ( Barry and Murphy, 2013 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%